ANALISIS KEMAMPUAN MATEMATIKA DASAR DITINJAU DARI SELF-REGULATED LEARNING: STUDI KASUS PADA MAHASISWA SI FARMASI UNIVERSITAS MATHLA’UL ANWAR PANDEGLANG BANTEN - Andri Imam Subekhi; Heni Pujiastuti (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2020)
The aims of this study to analyze students basic mathematical ability in terms of students self-regulated learning (high, medium, low). This research was a descriptive qualitative research. The subjects of this study were all students of the Department of Pharmacy totaling 30 people consisting of 12 men and 18 women. To obtain data in this study used research instruments consisting of two types, namely tests and non-tests. The test instrument was a basic mathematical ability test consisting of 10 problem questions and a non-test instrument in the form of an independent learning questionnaire. Analysis of students basic mathematical ability was analyzed using a score technique and then asked for grades ranging from 0 to 100. The scores were then classified as minimum completeness criteria (MCC). Analysis of basic mathematical ability data in terms of self-regulated learning was categorized into high, medium, and low. The results of this study indicate how to study mathematics S1 Pharmacy students at Mathla'ul Anwar Pandeglang University Banten still in the medium category with an average value of 46.67%.